2018
DOI: 10.1364/boe.9.005719
|View full text |Cite
|
Sign up to set email alerts
|

Small separation diffuse correlation spectroscopy for measurement of cerebral blood flow in rodents

Abstract: Diffuse correlation spectroscopy (DCS) has shown promise as a means to noninvasively measure cerebral blood flow in small animal models. Here, we characterize the validity of DCS at small source-detector reflectance separations needed for small animal measurements. Through Monte Carlo simulations and liquid phantom experiments, we show that DCS error increases as separation decreases, although error remains below 12% for separations > 0.2 cm. In mice, DCS measures of cerebral blood flow have excellent intra-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 84 publications
3
18
0
Order By: Relevance
“…37 Fits were constrained to g 2 ðr ¼ 1 cm; τÞ > 1.005 and g 2 ðr ¼ 2.5 cm; τÞ > 1.2 to increase sensitivity to the extracerebral and cerebral layers, respectively. 40,41 For all these fits, we assumed an index of refraction of 1.4, and we input the FDNIRS-estimated reduced scattering (μ 0 s ) and absorption (μ a ) coefficients at 852 nm of the corresponding hemisphere in which DCS was measured (see Sec. 6).…”
Section: Dcs Data Analysismentioning
confidence: 99%
“…37 Fits were constrained to g 2 ðr ¼ 1 cm; τÞ > 1.005 and g 2 ðr ¼ 2.5 cm; τÞ > 1.2 to increase sensitivity to the extracerebral and cerebral layers, respectively. 40,41 For all these fits, we assumed an index of refraction of 1.4, and we input the FDNIRS-estimated reduced scattering (μ 0 s ) and absorption (μ a ) coefficients at 852 nm of the corresponding hemisphere in which DCS was measured (see Sec. 6).…”
Section: Dcs Data Analysismentioning
confidence: 99%
“…al. showed the validity of diffusion approximation at short source‐detector separations by comparing with Monte Carlo simulations and liquid phantom experiments. For source‐detector separations larger than 3 mm, there was less than 5% error in α D b .…”
Section: Discussionmentioning
confidence: 96%
“…The first set of simulations consisted of 210 runs modeling different semi-infinite media with each run producing g 1 (τ) for 20 SDS (uniformly spaced between 0.1-2 cm). The optical properties of the media simulated obtained by permuting through five scattering coefficients (µ s : 3 − 15 cm −1 ), seven absorption coefficients (µ a : 0.05 − 0.5 cm −1 ) and six Brownian flow coefficients (D B : 5 × 10 −9 -3 × 10 −8 cm 2 /s) following the ranges as reported recently [31]. These MC simulations were compared against theoretical calculations to assess both the predictions of theory (forward model), as well as parametrization of the simulations (inverse model), as described in Section 2.4.…”
Section: Semi-infinite Modelsmentioning
confidence: 99%
“…However, there could be clinical opportunities for using endoscopically compatible DCS probes to assess tissue perfusion in vivo, which will need to use short SDS for signal acquisition. Further, recent reports have employed DCS measurements at short SDS (<1 cm) for quantifying tissue perfusion in small animal models [27][28][29][30][31]. Surprisingly, these studies all reported that the classical diffusion-theory based theoretical expression in Equation (2) still provided good parametrization of relative changes in tissue perfusion even at short SDS used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation